Nuevas perspectivas sobre la transnacionalidad del cine hispánico - Lefere, Robin; Lie, Nadia (Foro hispánico, 2016)
"This is the first book-length introduction in Spanish to the current debate on transnationality in Spanish and Latin American cinema, with theoretical and analytical contributions by several of the leading scholars in the field. = Éste es el primer libro en español que se dedica enteramente a plantear el debate contemporáneo acerca de la transnacionalidad del cine español y latinoamericano, con aportaciones teóricas y críticas que ofrecen algunos de los mejores especialistas"--Provided by publisher.